Group portrait of the attendees of the 8th Annual Methodist Layman's Retreat in Mission Springs, California - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the 8th Annual Methodist Layman's Retreat, held May 17-18, 1941 in Mission Springs, California. The all-male group is assembled out of doors in front of an unidentified residential building.